2020
DOI: 10.1093/ofid/ofaa040
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Potential Drug–Drug Interactions in the Changing Field of HCV Therapy

Abstract: Background With the introduction of direct-acting antivirals (DAAs) for hepatitis C virus (HCV) infection, drug–drug interactions (DDIs) emerged as significant challenge. Since then, HCV therapy and the infected population have rapidly changed. So far, very limited data are available regarding the clinical relevance of DDIs when using most modern DAA regimens. We aimed to assess how the importance of DDIs has evolved over time. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
1
19
0
1
Order By: Relevance
“…25 The results of our study regarding potential DIs with statins have also been reported in other published studies. 26 …”
Section: Discussionmentioning
confidence: 99%
“…25 The results of our study regarding potential DIs with statins have also been reported in other published studies. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, any selection of DAA regimens for older HCV patients should be made carefully. In addition, potential drug-drug interactions (DDIs) should not be underestimated or ignored, especially in the ritonavir-based regimen (35). Our results provide evidence that the presence of these comorbidities in older patients is not a barrier to achieving a SVR.…”
Section: Discussionmentioning
confidence: 76%
“…Although it is not possible to compare recommendations to avoid DDIs across studies, failure to follow recommendations to avoid DDIs was also seen in a significant proportion of patients (40%) in a large real-world study. 17 In the future, it will be important to collect specific reasons for not accepting recommendations to explore potential avenues for reducing potential DDIs. Awareness of DDIs is of paramount importance, and care could also be improved by inclusion of the Hepatitis Drug Interaction Database as a resource for pharmacists along with currently used sources (Micromedex, Facts and Comparisons, UpToDate, Lexicomp, and package inserts).…”
Section: Characteristics Of Patients Receiving Pharmacist Recommendationsmentioning
confidence: 99%
“…DDIs with lipid-lowering agents have previously been reported to be most frequent with regimens containing NS34A serine protease inhibitors. 17 EMR and pharmacy data suggest that population characteristics are highlight the importance of safety considerations and individualized therapies even for pangenotypic DAA regimens for chronic HCV, especially as treatment is expanded to high-risk populations to meet the WHO goal of HCV elimination.…”
Section: Characteristics Of Patients Receiving Pharmacist Recommendationsmentioning
confidence: 99%